The Influence of Audiovisual Media on Understanding Drama Material Class XI Makale Christian High School - Della Delfia Mandila; Anastasia Baan; Berthin Simega (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
The Indonesian nation is a nation that has many tribes that have created various regional languages. This diversity certainly requires Indonesian as a unifying language. Indonesian is one of the general subjects in schools. The scope of Indonesian language material from the learning achievement elements is literature which is understanding, appreciation, response, analysis, and creation of works. This learning process sometimes faces obstacles, one of which is the analysis activity. One of the media that is expected to help students in achieving a learning goal is audiovisual media. Through this study we will find out how audiovisual media influences learning to analyze drama. The type of research used is a quantitative approach. The population for this study was all class XI of SMA Kristen Makale with a total of 200 students and the sample was class XI-3 and X1-6 totaling 69 people. The results of this study indicate that audiovisual media can influence students' conceptual understanding of drama material by looking at the ability to analyze the concept of the material before using audiovisual media, students of class XI SMA Kristen Makale did not achieve the minimum learning completeness by looking at the average obtained by students, which is 80.29 while the completeness value that must be achieved is 86 while the ability to analyze the concept of the material after using audiovisual media, students of class XI SMA Kristen Makale have achieved the minimum learning completeness by looking at the average value obtained by students, which is 87.62. This is proven by the hypothesis test of the p-value <0.05, which is 0.000 <0.05, so it can be determined that Ho is rejected and Ha is accepted.